2008
DOI: 10.2138/am.2008.2719
|View full text |Cite
|
Sign up to set email alerts
|

57Fe Mossbauer study of the oxidation state of iron in stilpnomelane from granite pegmatites in Poland

Abstract: The effects of heat treatment on stilpnomelane from granite pegmatites at Zółkiewka (Lower Silesia, Poland) were studied using 57 Fe Mössbauer spectroscopy. Samples of naturally altered stilpnomelane and chlorite were also studied. The Mössbauer spectrum of an untreated sample was fitted to two Fe 2+ doublets and two Fe 3+ doublets. The Fe 2+ doublets had similar isomer shifts (1.13 and 1.16 mm/s for the octahedral M1 and M2 sites), different quadrupole splitting values (QS = 2.28 and 2.66 mm/s, respectively),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Fe(II) and Fe(III) are usually differentiated by the wet chemistry technique. [3 -5] To measure Fe(II) and Fe(III) contents in separated minerals, the methods of nuclear gammaresonance (for example, refs [6,7]) and X-ray absorption near edge structure (XANES) (for example, refs [8,9]) can also be employed. The position of the peak and intensity of some characteristic lines of emission of the X-ray spectrum are affected by the chemical bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Fe(II) and Fe(III) are usually differentiated by the wet chemistry technique. [3 -5] To measure Fe(II) and Fe(III) contents in separated minerals, the methods of nuclear gammaresonance (for example, refs [6,7]) and X-ray absorption near edge structure (XANES) (for example, refs [8,9]) can also be employed. The position of the peak and intensity of some characteristic lines of emission of the X-ray spectrum are affected by the chemical bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of sodic amphiboles, Li contents, measured by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), were considered where available in the computed formulae. Biotite formulae and classification are according to Rieder et al (1998), whereas the schemes suggested by Zang and Fyfe (1995), Guggenheim et al (2007) and Yavuz et al (2015), and those by Hutton (1938) and Malczewski and Popiel (2008) were applied for chlorite and stilpnomelane, respectively.…”
Section: Analytical Procedures and Data Treatmentmentioning
confidence: 99%
“…3), which is also identified in each basalt sample, most probably may be assigned to hornblende [3,6]. Hornblende (Ca,K,Na) 2-3 (Mg,Fe 2+ ,Fe 3+ ,Al) 5 (Si,Al) 8 O 22 (OH) 2 represents the amphiboles that is an important group of inosilicate rock-forming minerals, which occur in igneous and metamorphic rocks [2,4].…”
Section: Basaltsmentioning
confidence: 99%
“…Hematite may be regarded as a secondary mineral in this type of rock and can be formed by the weathering of primary iron-bearing minerals or regional metamorphism [1,5]. 8 , a micaceous greenish mineral, is common in low-grade schist or as the alteration product of pyroxenes or amphiboles [5]. Chlorite phase was also identifi ed in the WGK sample (doublets no.…”
Section: Pillow Lavasmentioning
confidence: 99%